0930 Prenatal Cannabis Use and Sleep Outcomes in Children 9-10 Years of Age in the Adolescence Brain Cognitive Development Study. (27th May 2020) - Winiger, E; Hewitt, J
Abstract: Introduction: The fetal brain is densely populated with CB1 receptors that increase in number throughout gestation and might be involved in sleep processes since they are found in many brain areas related to the regulation of the sleep-wake cycle. THC binds to CB1 receptors, possibly altering neurodevelopment and fetal cortical circuitry in the womb. Studies have found prenatal cannabis use is associated with early sleep factors from as early as few days after birth to 3 years of age, yet no studies have examined associations in later childhood. Methods: We used data from the Adolescent Brain Cognitive Development (ABCD) study to determine whether maternal reports of cannabis use while pregnant were associated with child sleep outcomes (The Sleep Disturbance Scale for Children) among 11, 875 children ages 9-10. Regression analyses accounted for the nested nature of families (twin and non-twin sibling) and were estimated controlling for potential covariates including daily tobacco and weekly alcohol use during pregnancy, mother's education, combined household income, parental marital status, child sex, and child age. Results: Amongst mothers in our sample, 6% endorsed using cannabis while pregnant. Prenatal cannabis use was associated with lower sleep duration, disorders of initiating and maintaining sleep, disorders of arousal, sleep wake disorders, disorders of excessive somnolence, and a summed sleep score (all b >0.09 and p < 0.04) but not with sleep latency, sleep breathing disorders, and sleep hyperhidrosis (all b <0.08 and p >0.09). Conclusion: Prenatal cannabis use was associated with increased childhood sleep deficits including shorter sleep duration and higher endorsements of sleep disorder symptoms. This is the first report of prenatal cannabis use being associated with sleep in childhood as late as 9-10 years of age. Although causality is not established, the results suggest potential long-term effects of prenatal cannabis use on sleep and the need for abstinence from cannabis use while pregnant. Support: T32 DA017637. The ABCD Study is supported by the National Institutes of Health and additional federal partners under award numbers U01DA041022, U01DA041028, U01DA041048, U01DA041089, U01DA041106, U01DA041117, U01DA041120, U01DA041134, U01DA041148, U01DA041156, U01DA041174, U24DA041123, U24DA041147, U01DA041093, and U01DA041025 (https:// abcdstudy.org/federal-partners.html).